The invisible bridge : the fall of Nixon and the rise of Reagan - Perlstein, Rick, 1969- (Simon & Schuster, 2014)
The best-selling author of Nixonland presents a portrait of the United States during the turbulent political and economic upheavals of the 1970s, covering events ranging from the Arab oil embargo and the era of Patty Hearst to the collapse of the South Vietnamese government and the rise of Ronald Reagan.